Cognitive Processes of ESL Learners in Pragmatic Role-Play Tasks in Academic Settings - Bi, Nick Zhiwei (Frontiers in Psychology, 2021)
The purpose of the study was to investigate the cognitive processes of English as second language (L2) learners that are involved in their task-based pragmatic performances in academic settings. This study, therefore, examined the cognitive processes of 30 English L2 learners when engaging in various role-play-based pragmatic performances, such as requesting a recommendation letter from a professor and negotiating an agreeable meeting time with classmates. The qualitative analyses of the retrospective verbal reports (RVRs) data of the participants indicated that the learners employed a series of cognitive, metacognitive, and pragmatic strategies when accomplishing various speech acts (e.g., requests and refusals). This study hoped to make two new contributions to the field. First, the study provided empirical evidence to validate the theoretical taxonomy of the strategy use of learners in L2 pragmatics. Additionally, the theoretical foundations of current research on cognitive processes are primarily informed by pragmatic theories. Thus, the study aims to explicate a more comprehensive view of the cognitive processes of L2 learners in pragmatic performances by employing the theories from both pragmatic and learner strategy perspectives.